The design and impact of culturally-safe community-based physical activity promotion for immigrant women: descriptive review - Anna R. Gagliardi; Ciara Morrison; Natalie N. Anderson (BMC, 2022)
Abstract Background Immigrant women have low rates of physical activity (PA), placing them at risk for chronic diseases. Some research suggests that strategies targeting this group must be culturally-safe and community-based. This study aimed to identify the design (i.e. characteristics) and impact of culturally-safe community-based PA promotion for immigrant women. Methods We conducted a descriptive review by searching MEDLINE, EMBASE, SPORTDiscus, CINAHL, SCOPUS, Cochrane Library and Joanna Briggs Institute Database of Systematic Reviews from inception to June 9, 2021 for English language studies that assessed community-based PA promotion strategies targeting adult immigrants and involved at least 50% women. We compiled findings in a preliminary context-mechanisms-outcomes conceptual framework. Results We included 13 studies published from 2004 to 2020. Three included women-only; the remainder included a median of 63% women (range 50 to 98%). Studies included immigrants from Brazil, Dominican, Columbian, Haiti, Mexico, China, Vietnam, Bangladesh, India, Pakistan, Somalia, Sudan and Turkey. All but one study (89%) significantly improved one or more outcomes: PA knowledge, PA participation and anthropometric measures (e.g. weight, BMI, blood pressure). Most (89%) strategies were multi-faceted: in-person group educational sessions reinforced by take-home educational material and/or follow-up reminder phone calls. Single strategies (e.g. mailed educational material, group educational session) also achieved beneficial outcomes. We identified 17 culturally-safe characteristics of PA promotion strategies: language of choice, based in community settings or organizations, led by lay health workers, reflected ethno-cultural linguistic expressions and PA norms, and recognized and offered solutions to barriers of PA. Findings were captured in a preliminary theory of how contextual factors (gender, intersectionality) and mechanism (culturally-safe PA promotion) may influence PA-related outcomes (PA knowledge, self-efficacy and participation; anthropometric measures, quality of life). Conclusions This study revealed the characteristics of PA promotion strategies that significantly improved PA-related outcomes among immigrants. Given that few studies focused solely on immigrant women or reported sub-analyses, the conceptual framework generated by this study can be used in future research to more definitively establish the design and impact of culturally-safe, community-based PA promotion for immigrant women.